Impact of COVID‐19 Pandemic Lockdown in Ambient Concentrations of Aromatic Volatile Organic Compounds in a Metropolitan City of Western India. Issue 6 (23rd March 2022) - Sahu, L. K.; Tripathi, Nidhi; Gupta, Mansi; Singh, Vikas; Yadav, Ravi; Patel, Kashyap
Abstract: The real‐time Benzene, Toluene, Ethylbenzene, and Xylenes (BTEX) concentrations were measured in a metropolitan city of India during January to May of 2020 and 2014‐2015‐2018 to assess the impact of emission reduction during the COVID‐19 lockdown. The total BTEX (∑BTEX) concentrations were 11.5 ± 9.0, 15.7 ± 16, 5.3 ± 5.0, 2.9 ± 2.0, and 0.93 ± 1.2 ppbv in January–May 2020, respectively. The evening rush hour peaks of BTEX during lockdown decreased by 4–5 times from the same period of years 2014‐2015‐2018. A significant decline in background concentrations suggests a regional‐scale reduction in anthropogenic emissions. The contributions of ∑TEX compounds to ∑BTEX increased from 42% to 59% in winter to 64%–75% during the lockdown under hot summer conditions. While emission reductions dominated during the lockdown period, the meteorological and photochemical factors may also have contributed. Meteorological influence on actual observed BTEX data was removed by normalizing with ventilation coefficient (VC). The actual ambient air reductions of 85%–90% and VC‐normalized reductions of 54%–88% of the BTEX concentrations during lockdown were estimated compared to those during the same period of 2014‐2015‐2018. The estimated changes using nighttime data, which take into account BTEX photooxidation removal, are ∼8% lower than the VC‐normalized estimates using all data. These significant reductions in BTEX concentrations are consistent with the change in people's movement as inferred from mobility data during the lockdown. Although enforced, the significant decline in ambient BTEX levels during lockdown was a good change for the air quality. The study suggests a need for more effective science‐based policies that consider local and regional factors. Plain Language Summary: Outbreaks of the COVID‐19 pandemic necessitated the implementation of strict lockdown in India, which drastically decreased anthropogenic emissions. The elevated levels of a group of aromatic volatile organic compounds known as benzene, toluene, ethylbenzene, and xylenes (BTEX) can adversely impact human health. The real‐time continuous measurements of ambient air BTEX concentrations were conducted in a major city of India during January–May 2020. The concentrations of all BTEX compounds declined drastically during the COVID‐19 lockdown period. We incorporated the VC in the ambient air BTEX concentrations to reduce the meteorological influences. During the lockdown, different BTEX compounds were reduced by 54%–88% compared to the same period during the normal years. In addition to reduced anthropogenic activities, the balance between photochemical processes and evaporative emissions seems to control BTEX concentration and composition during the lockdown period. Although enforced, the decrease of ambient BTEX concentrations was a good change for air quality as these compounds are primary pollutants and precursors for secondary pollutants. This is the most comprehensive study, investigating the impact of the lockdown on ambient BTEX concentrations in India. Key Points: Significant reductions in ambient benzene, toluene, ethylbenzene, and xylenes (BTEX) concentrations during COVID‐19 lockdown in a major city of India Meteorology‐corrected BTEX concentrations during lockdown‐2020 decreased by 54%–88% from the same period of 2014–2015–2018 The estimates accounting for the photo oxidation removal cause lesser reductions by ∼8% than ventilation coefficient‐normalized estimates